Stepping into the future: unveiling biomechanical innovations in 3d printed footwear design - Lu, Z.; Xin, L.; Hairong, C.; Qiaolin, Z.; Gusztáv, F.; András, K.; Yaodong, G. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: The three-dimensional (3D) printing technology, developed over the past 40 years since its invention in the 1980s, has found extensive applications across various manufacturing industries. Its distinctive customization and flexibility hold the potential to overcome traditional design constraints, garnering significant attention in the creation of personalized footwear. Despite lower initial awareness among early industries and consumers, recent research, utilizing advanced techniques, delves into the biomechanical performance of 3D-printed footwear, offering renewed hope. This review explores the progress of 3D printing technology in the footwear manufacturing sector from a biomechanical perspective. The research primarily focuses on the performance of 3D-printed footwear in terms of sports injuries, comfort, and athletic performance. Despite existing limitations, an in-depth exploration of the potential of 3D printing technology in the footwear manufacturing domain is expected to provide new insights and momentum for future development. METHODS: This systematic review was conducted in accordance with the recommendations outlined in the Joanna Briggs Institute (JBI) Reviewers Manual and the PRISMA 2020 guidelines. A fuzzy literature search was performed on October 4, 2023, using the search terms ("3D print" OR "additive manufacture") AND ("shoe" OR "footwear" OR "insole" OR "midsole" OR "sole") across the Web of Science, PubMed, and Scopus databases. Methodological quality assessment was performed using the quantitative evaluation tool developed by Kmet. RESULTS: After retrieving 1671 articles, an additional 14 articles were identified through citation analysis. Ultimately, 23 studies were included in the comprehensive review. The primary reason for low-quality scores was the failure to report the use of blinding, randomization, and incomplete control of confounding factors. Overall, the majority of studies observed superior performance of 3D printed products in terms of sports injuries, comfort, and athletic performance. However, a minority of studies suggested that in certain indicators, these products may not surpass traditional counterparts. CONCLUSION: Despite controversies surrounding midfoot pressure distribution and comfort, 3D printing technology has the capability to manufacture footwear that meets individual needs. This includes reducing pressure and impact, enhancing motion control performance, and improving gait stability. The comfort of 3D printed footwear, particularly those designed based on plantar pressure, has demonstrated positive outcomes in the medium to long term, with potential advantages observed in running and jumping activities. Future research should fully leverage technological advantages, integrating advanced machine learning algorithms and finite element analysis techniques. Addressing deficiencies in research design is imperative, and there is a need to promote hypothesis-driven studies in the field.